2022
DOI: 10.1590/fst.45322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air drying temperature on the phenolics and antioxidant activity of Xuan-Mugua fruit

Abstract: Xuan-Mugua is a Chinese traditional fruit and is mainly preserved by air drying. To explore the effect of temperature on the drying property and quality of the fruits, they were sliced and dried at 60-90 °C. The results indicated that the drying time shortened from 150 to 80 min with the increasing temperature and the minimal time was found at 90 °C. The total phenolic content and antioxidant activity generally decreased by 5.09-18.27% at higher temperature (90 °C) and their maximums respectively appeared at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several researchers have conducted experimental studies on the effects of drying on antioxidant activity, coming to the conclusion that raising the drying temperature reduces the nutritional characteristics [103][104][105][106][107][108]. Related studies have looked into how different drying techniques (primarily vacuum drying, freeze drying, and hot air drying) affect the antioxidant content of fruits [109,110].…”
Section: Influence Of Drying Temperature On Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have conducted experimental studies on the effects of drying on antioxidant activity, coming to the conclusion that raising the drying temperature reduces the nutritional characteristics [103][104][105][106][107][108]. Related studies have looked into how different drying techniques (primarily vacuum drying, freeze drying, and hot air drying) affect the antioxidant content of fruits [109,110].…”
Section: Influence Of Drying Temperature On Antioxidant Activitymentioning
confidence: 99%
“…Recent research by Chen et al revealed that although the content of total phenolic compounds and antioxidant activity of the samples generally decreased with increasing drying temperatures, the content of specific phenols varied with drying temperature, and chlorogenic acid underwent a clear transformation at higher temperatures (80-90 • C). The authors also reported that the ideal drying temperature for Xuan-Mugua fruit slices was 70 • C, considering the phenolic profile and concentration as well as the antioxidant activity [108].…”
Section: Influence Of Drying Temperature On Antioxidant Activitymentioning
confidence: 99%
“…The observed behavior of CT and E-CTC towards drying does not coincide with those of early findings of Madrau et al [38], reporting a substantial reduction in these biactives after convective drying of apricot fruit at 55 and 75 • C. This is the first report highlighting the increase of bioactives, CT and E-CTC, in particular, observed after apricot fruit osmotic dehydration and convective drying. However, an increase in the concentration of individual bioactives as a result of convective drying was noted by many authors in fruit such as kiwi (Actinidia deliciosa), pepino (Solanum muricatum Aiton) [86], black rosehip (Rosa pimpinellifolia) fruit [87], as well as Xuan-Mugua (Chaenomelis Fructus) [88], and avocado (Persea americana Mill.) [89].…”
Section: The Content Of Individual Phenolic Compounds In Apricot Frui...mentioning
confidence: 99%
“…The drying temperature and vacuum pressure increased with decreasing the drying time. Chen et al (2022) explored the temperature effect of oven drying on the drying property and quality of Xuan-Mugua fruit; Ataides et al (2022) dried epicarps of araticum fruits at different temperatures with oven drying; and Silva et al (2022) dried Brazil nuts with a forced ventilation oven. Their results revealed the higher temperature the quicker the drying time that corresponds to a recent research result.…”
Section: Drying Characteristicmentioning
confidence: 99%